FORMATION OF THE TASHKENT FINANCIAL CENTER WITHIN THE FRAMEWORK OF THE “UZBEKISTAN-2030” STRATEGY - Supervisor: PhD Akhmadaliyeva Nikhola; Student: Ganijonova Muxlisaxon (The Conference Hub, 2025)
The International Financial Center is supported by the fact that the “New Uzbekistan-2030” strategy specifically highlights the creation of an IFC in Tashkent. This platform should not only enhance the aesthetic appearance of the capital, but also help the country strengthen its ties with neighboring states and establish direct access to the global financial system.
Keywords: Tashkent international financial center, stock exchange, banking sector, personnel development